1991
DOI: 10.1128/mcb.11.10.4903
|View full text |Cite
|
Sign up to set email alerts
|

v-Src increases diacylglycerol levels via a type D phospholipase-mediated hydrolysis of phosphatidylcholine.

Abstract: Activating the protein-tyrosine kinase of v-Src in BALB/c 3T3 cells results in rapid increases in the intracellular second messenger, diacylglycerol (DAG). v-Src-induced increases in radiolabeled DAG were most readily detected when phospholipids were prelabeled with myristic acid, which is incorporated predominantly into phosphatidylcholine. Consistent with this observation, v-Src increased the level of intracellular choline. No increase in DAG was observed when cells were prelabeled with araehidonic acid, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 42 publications
6
76
1
Order By: Relevance
“…PLD activity has been reported to be elevated in cells transformed by v-Src (Song et al, 1991), v-Ras (Jiang et al, 1995a), and v-Raf . PLD activity is also elevated in response to mitogens including platelet-derived growth factor (Plevin et al, 1991), epidermal growth factor (Song et al, 1994), and insulin (Shome et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PLD activity has been reported to be elevated in cells transformed by v-Src (Song et al, 1991), v-Ras (Jiang et al, 1995a), and v-Raf . PLD activity is also elevated in response to mitogens including platelet-derived growth factor (Plevin et al, 1991), epidermal growth factor (Song et al, 1994), and insulin (Shome et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Lipids were extracted and analyzed as previously described [15] with minor modifications. Reactions were stopped by quickly pouring off the medium and treating the cells with 600 l of ice-cold CH 3 OH/ 6 N HCl (50:2, v:v).…”
Section: Determination Of Pld Activity and The Production Of Dagmentioning
confidence: 99%
“…Many growth factors for receptor tyrosine kinases, including the epidermal growth factor (EGF), platelet-derived growth factor (PDGF), v-Src, fibroblast growth factor (FGF), and insulin-like growth factor (IGF), have been shown to activate PLD activity [9][10][11][12][13][14]. Activation of non-receptor tyrosine kinase v-Src has also been shown to activate PLD activity [15]. The involvement of protein kinase C in the regulation of PLD activity has been intensively studied in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling pathways activated by v-Src and v-Ras (Burgering and Bos, 1995) include those involving phosphatidylinositol-3-kinase (Carpenter and Cantley, 1996), protein kinase C (Song et al, 1991), Raf-1 (Blobe et al, 1994) the extracellular regulated kinases (ERK-1 and 2) (Burgering and Bos, 1995) and phospholipase D (PLD) (Song et al, 1991). It has been reported that Raf-1, MEK-1 and ERK1 mediate the signal leading to uPA, uPA receptor, and MMP-9 upregulation Gum et al, 1997).…”
Section: Introductionmentioning
confidence: 99%